Improving English Oral Communication through Multimodal Learning Strategies for Secondary School Students - Aya Ragab; Nur Arifah Drajati; Eka Bhudi Santosa (Universitas Negeri Semarang, 2025)
Background – The rapid integration of digital technologies and artificial intelligence (AI) in education presents both opportunities and challenges, especially in improving English oral communication and promoting ethical digital behavior. AI-driven multimodal platforms that combine visual, auditory, reading/writing, and kinesthetic modes offer inclusive learning, but teachers must develop ethical, reflective, and collaborative competencies to ensure responsible AI use. Issues such as digital inequality, limited infrastructure, and insufficient professional development highlight the need for innovative frameworks aligned with Kurikulum Merdeka. Purpose – This study aims (1) to design and analyze a conceptual framework for an AI-driven multimodal learning platform that personalizes English oral communication, provides real-time feedback, and strengthens students’ digital citizenship; and (2) to identify essential teacher competencies and challenges related to AI integration to guide sustainable professional development. Method/Approach – A qualitative conceptual design was applied by synthesizing literature on multimodality, AI in education, teacher competence, and digital citizenship. This was supported by a systematic literature review (SLR) of 12 Scopus-indexed articles (2020–2025) using the keywords “Artificial Intelligence,” “teacher competence,” “AI in education,” and “TPACK.” Thematic analysis with iterative coding ensured analytical reliability. Findings – The proposed multimodal–AI framework shows strong potential to enhance oral communication through AI-enabled personalization, speech-recognition feedback, and interactive multimodal tasks. The review identifies three core teacher competency domains: AI literacy and ethical awareness, data-driven digital pedagogical design, and collaborative reflective practice. Major challenges include limited infrastructure, unequal digital access, ethical concerns, and inadequate AI-focused training. Conclusion – Adopting AI–TPACK, design thinking, and growth-mindset principles can guide effective professional development in multimodal–AI learning environments. Novelty/Originality/Value – The study’s originality lies in integrating language proficiency and ethical digital citizenship within a unified multimodal–AI framework, offering theoretical contributions and practical direction for future educational innovation.